2021
DOI: 10.4103/1735-5362.319575
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of kaempferol glycosides isolated from Cedrela odorata L. leaves in albino mice

Abstract: Background and purpose: Paracetamol is the most implicated xenobiotic in inducing hepatotoxicity. Our study aimed to determine the impact of some kaempferol glycosides isolated from the leaves of Cedrela odorata L. on paracetamol hepatotoxicity. Experimental approach: The methanolic extract of dried leaves of C. odorata L . was subjected to the combination of spectroscopic methods ( 1 H and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(90 reference statements)
1
6
0
Order By: Relevance
“…Interestingly, pretreatment with KSG significantly alleviated the pathological lesions and reduced the elevated levels of transaminases, ALP, LDH, and γ-GT, indicating protection of the liver's integrity and function by KSG. Importantly, the hepatoprotective activity of different derivatives of kaempferol against experimental hepatic injury has been shown previously [ 30 , 31 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, pretreatment with KSG significantly alleviated the pathological lesions and reduced the elevated levels of transaminases, ALP, LDH, and γ-GT, indicating protection of the liver's integrity and function by KSG. Importantly, the hepatoprotective activity of different derivatives of kaempferol against experimental hepatic injury has been shown previously [ 30 , 31 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 78%
“…For instance, flavonoids compounds such as catechin and kaempferol fight against free radicals and inhibit liver disease pathogenesis (Okaiyeto et al, 2018). Also, glycosides act as an antioxidant to provide hepatoprotective efficacy (Asaad et al, 2021; Siddiqui et al, 2018). Besides, (Huang et al, 2014) reported the hepatic protection of triterpenoids and saponins.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, flavonoids compounds such as catechin and kaempferol fight against free radicals and inhibit liver disease pathogenesis (Okaiyeto et al, 2018). Also, glycosides act as an antioxidant to provide hepatoprotective efficacy (Siddiqui et al, 2018;Asaad et al, 2021). Besides, (Huang et al, 2014), reported the hepatic protection of triterpenoids and saponins.…”
Section: Discussionmentioning
confidence: 99%